Klinický význam nových metod v echokardiografii : význam tkáňové dopplerovské echokardiografie pravé komory u pacientů se srdečním selháním - Kincl, Vladimír (2007)
Aim: Using of tissue doppler imaging in heart failure risk stratification Methods: In all, 140 patients with symptomatic heart failure and mean ejection fraction of 24% underwent standard echocardiographic examination, Doppler tissue imaging of tricuspid annular motion when parameters Sa, Ea, Aa, IVA and RV Tei index were evaluated and right heart catheterization. The patients were followed up for cardiac related death and non-fatal cardiac events including the implantation of cardioverter-defibrillator and hospitalization for heart failure decompensation. There was performed subsequent analysis of 108 patients when only parameters RV Tei index , IVA and RV IVRT were analysed, and later was add 51 patients without follow-up, correlation a and comparative analyses were perfomed on group of 191 persons. Results: The most powerful prognostic value have combinations Sa ≤10,8 cm/s, Ea ≤ 8,9 cm/s and Tei index ≥1,20 for risk of cardiac death and Ea ≤ 8,9 cm/s with IVA ≤ 2,52 m/s2 for ri.